2010
DOI: 10.1007/s10519-010-9372-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Polymorphisms of the Dopamine Receptor D2 and Catechol-o-Methyl Transferase Genes and Cognitive Function

Abstract: The dopaminergic neurotransmitter system of the brain is involved in working memory and other cognitive functions. Studies suggest an important role for dopamine synthesis and uptake in modulation of human cognitive processes. We studied the association between polymorphisms in the catechol-o-methyl transferase (COMT) and dopamine receptor D2 (DRD2) genes and general cognitive ability in a secondary analysis of 2091 men and women, aged 55-80 years living in Scotland. General cognitive ability 'g' was derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
(61 reference statements)
2
32
0
Order By: Relevance
“…This issue is of theoretical significance because other indices, such as fluid intelligence, have also been associated with intraindividual variability (Li et al, 2004Rabbitt, Osman, Moore, & Stollery, 2001;Ram et al, 2005) and dopamine neuromodulation (e.g., Bäckman et al, 2000;Bolton et al, 2010;Volkow et al, 1998). Direct comparisons of the associations of variability measures and other indices of cognitive performance to dopamine neuromodulation are needed to shed light on this issue.The present study makes two novel contributions to the existing literature on performance variability.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of theoretical significance because other indices, such as fluid intelligence, have also been associated with intraindividual variability (Li et al, 2004Rabbitt, Osman, Moore, & Stollery, 2001;Ram et al, 2005) and dopamine neuromodulation (e.g., Bäckman et al, 2000;Bolton et al, 2010;Volkow et al, 1998). Direct comparisons of the associations of variability measures and other indices of cognitive performance to dopamine neuromodulation are needed to shed light on this issue.The present study makes two novel contributions to the existing literature on performance variability.…”
Section: Discussionmentioning
confidence: 99%
“…Such cognitive benefits have been found to correlate with lower brain activation, indicating more efficient information processing (Egan et al 2001;Sambataro et al 2009). However, several studies have failed to replicate these findings (Blanchard et al 2011;Bolton et al 2010;Stuart et al 2014), and two meta-analyses only documented a COMT Met superiority on measures of general cognition, such as IQ (Barnett et al 2007(Barnett et al , 2008.…”
Section: Comt Polymorphismmentioning
confidence: 99%
“…The genetic studies looking at the association of DRD2 C957T with cognitive function have generally shown that CC homozygosity is associated with poorer performance on tests of executive function and working memory in the general population (Rodriguez‐Jimenez et al., 2006; Xu et al., 2007), decreased general cognitive ability in elderly healthy males and females (Bolton et al., 2010), impaired executive function and cognitive flexibility in HIV‐infected individuals who abuse alcohol (Villalba, Devieux, Rosenberg, & Cadet, 2015), and poorer performance in an attentional switching task in CC homozygotic females (Gurvich & Rossell, 2015). The T allele and TT homozygosity has been associated with better avoidance learning from negative outcomes in both forced choice and reaction time tasks (Frank, Doll, Oas‐Terpstra, & Moreno, 2009; Frank, Moustafa, Haughey, Curran, & Hutchison, 2007), better striatally mediated reflexive learning (Xie, Maddox, McGeary, & Chandrasekaran, 2015) and rule‐based category learning in healthy young adults (Byrne, Davis, & Worthy, 2016), and with superior performance in an attentional switching task in TT homozygotic males (Gurvich & Rossell, 2015).…”
Section: Introductionmentioning
confidence: 99%